PELATIHAN DESAIN GRAFIS DAN FOTONOVELA UNTUK WARGA DESA NGEMBAL KEC. WAJAK KAB. MALANG - Rini Agustina; Dodit Suprianto (Universitas Padjadjaran, 2018)
Technological developments are also very influential on community service institutions at the village level. The village currently has made many improvements in terms of service to the community, including one of which is service in terms of providing information. Information from the center must be immediately absorbed by the community as soon as possible given the deadline and time for each information submitted. The information provided will be very useful for the community for that it needs a quick and appropriate socialization. The purpose of this activity is to increase the creativity of villagers in making information and photo media with graphic designs to convey information to the community and other village activities in an effort to promote an activity. Training to make graphic and photo design becomes something that is very necessary to increase the creativity of the village leaders and the community they represent. The solution offered is to provide training assistance in graphic design and photography for the residents of Ngembal Village, Wajak District, Malang Regency.